A histologic, histomorphometric, and radiographic comparison between two complexes of CenoBoen/CenoMembrane and Bio-Oss/Bio-Gide in lateral ridge augmentation: A clinical trial - Babak Amoian; Ehsan Moudi; Maryam Seyed Majidi; S M Ali Tabatabaei (Wolters Kluwer Medknow Publications, 2016)
Background: Several grafting materials have been used for alveolar ridge augmentation. The literature lacks researches to compare CenoBone to other grafting materials. The aim of this study was to compare CenoBone/CenoMembrane complex to Bio-Oss/Bio-Gide complex in lateral alveolar bone augmentation in terms of radiographic, histologic, and histomorphometric parameters. Materials and Methods: In this randomized controlled trial, ten patients who needed lateral ridge augmentation were selected and augmentations were done using either of CenoBone/CenoMembrane or Bio-Oss/Bio-Gide complexes. In the re-entry surgery in 6 months following augmentation, core biopsies were taken and clinical, radiographic, histologic, and histomorphometric evaluations were performed. Results: No statistically significant difference was seen between groups except for the number of blood vessels and percentage of residual graft materials. Conclusion: CenoBone seems to present a comparable lateral ridge augmentation to Bio-Oss in.